The physical chemist's toolbox - Metzger, R. M. (Robert M.) 1940- (Hoboken, New Jersey Wiley, 2012)
"This book is an indispensible guide for those in the fields of physics, chemistry, and materials science, addressing the relevant equations, theories, and tools used for research in these fields. Topics addressed are mechanics, special relativity, electricity and magnetism, quantum chemistry, thermodynamics, electrochemistry, statistical mechanics, symmetry, solid state physics and electronics. The book also addresses all possible energy and electrical sources, detectors, and algorithms, as well as all presently available major and minor instrumentation. There are also worked-out problems and suggested fill-in problems interspersed throughout"-- Provided by publisher.
Includes bibliographical references and index.
Keywords: Chemistry, Physical and theoretical